Assembly and recognition of keratins: A structural perspective. (August 2022) - Yu, Bowen; Kong, Dandan; Cheng, Chen; Xiang, Dongxi; Cao, Longxing; Liu, Yingbin; He, Yongning
Abstract: Keratins are one of the major components of cytoskeletal network and assemble into fibrous structures named intermediate filaments (IFs), which are important for maintaining the mechanical properties of cells and tissues. Over the past decades, evidence has shown that the functions of keratins go beyond providing mechanical support for cells, they interact with multiple cellular components and are widely involved in the pathways of cell proliferation, differentiation, motility and death. However, the structural details of keratins and IFs are largely missing and many questions remain regarding the mechanisms of keratin assembly and recognition. Here we briefly review the current structural models and assembly of keratins as well as the interactions of keratins with the binding partners, which may provide a structural view for understanding the mechanisms of keratins in the biological activities and the related diseases.